1019Socioeconomic inequities in 5-year weight trajectories in association with baseline weight-related perceptions: a longitudinal study. (2nd September 2021) - Feng, Xiaoqi; Wilson, Andrew
Abstract: Background: Recognition of overweight may be a necessary pre-cursor for weight-reduction, but some suggest under-perceiving overweight may be protective against obesity. Differential responses may occur across socioeconomic strata. Methods: Five-year body mass index (BMI) trajectories were examined using multilevel models of 8174 participants stratified by gender, neighbourhood socioeconomic circumstances, baseline BMI and perceived weight status, adjusting for potential confounders. Results: At baseline, weight-related dissatisfaction and perceived overweight were associated with higher mean BMI, regardless of whether people were classified as 'normal' or overweight by WHO criteria. Mean BMI did not decrease among people classified as overweight who perceived themselves as overweight, or expressed weight-related dissatisfaction. Among those with 'normal' BMI at baseline but dissatisfied with their weight, mean BMI increased disproportionately among people in disadvantaged areas. Mean BMI also rose disproportionately for people in disadvantaged areas among those feeling overweight, despite having a 'normal' BMI, compared to people with the same over-perception but living in affluent areas. Conclusions: No evidence was found to suggest accurate recognition of overweight or expressing weight-related dissatisfaction leads to a lower BMI. However, there was evidence of an increase in mean BMI among people who felt dissatisfied with, or over-perceived their 'normal' weight, especially in socioeconomically disadvantaged areas. Key messages: Correction of under-perceptions may not drive weight loss, but circumstances contributing to over-perception and dissatisfaction with weight status may contribute to increased weight gain and exacerbate socioeconomic inequities in BMI.